[18F]FDG PET/CT volumetric biomarkers for non-invasive prediction of HER2 expression in breast cancer patients - Mai ELahmadawy; Heba Abdelhameed; Dina Gamal El-din; Mahitab Eltohamy; Adel Hassan; Salwa Abd El-Gaid (Asia Oceania Journal of Nuclear Medicine and Biology)
Objective(s): to investigate the capability of 18F-fluorodeoxyglucose positron emission tomography/computed tomography ([18F]-FDG PET/CT) derived volumetric parameters to predict human epidermal growth factor receptor 2 (HER2) status in breast cancer patients.Methods: retrospective study enrolled 47 female patients with breast cancer. All patients had pretreatment [18F]-FDG PET/CT. Clinical data, pathology report and HER2 status were retrieved from medical records. In an attempt to assess the predictive value of the PET-derived metabolic parameters, Receiver operating characteristic (ROC) curve was constructed with area under curve analysis performed to detect best cutoff value of significant parameters for detection of HER2 positive.Results: No statistically significant difference was noted among both groups (HER2 positive and negative) in respect to age, menopausal status, histology, grade, T-stage, N-stage, or antigen Kiel 67 (Ki-67) index. ROC curve successfully marked cutoff point ≥42.35 for total lesion glycolysis (TLG) and ³12.75 for metabolic tumor value (MTV) that are capable to discriminate positive versus negative HER2 expression in breast cancer patients with area under curve (AUC) 0.728 and 0.723 and P-values 0.002 and 0.004 respectively. Such cutoff point was not deduced for standard uptake value (SUV) max. Primary tumor TLG cutoff correlated well with age where 77.8% of patients with TLG  ³42.35 were older than 45 years old compared to 22.2% of them who were younger than 45 years, P-value=0.047. Also 70.3% of patients with TLG exceeds  ³42.35 had T3 and 4 primary tumors while 65% of those with TLG <42.35 their primary tumors were T1 and 2, P-value=0.03. As regards Primary tumor MTV cutoff point, significant correlations were noted in respect to T-stage where 78.2% of the patients with primary tumor MTV ³12.75 were T3 and 4, compared to 66.6% of those with primary tumor MTV <12.75 were T1 and 2, P-value=0.011.Conclusion: PET-derived volumetrics may serve as non-invasive predictors of biological processes represented here as HER2 expression in breast cancer patients.